Optimized 5-Fluorouridine Prodrug for Co-Loading with Doxorubicin in Clinically Relevant Liposomes - Debra Wu; Douglas Vogus; Vinu Krishnan; Marta Broto; Anusha Pusuluri; Zongmin Zhao; Neha Kapate; Samir Mitragotri (MDPI AG, 2021)
Liposome-based drug delivery systems have allowed for better drug tolerability and longer circulation times but are often optimized for a single agent due to the inherent difficulty of co-encapsulating two drugs with differing chemical profiles. Here, we design and test a prodrug based on a ribosylated nucleoside form of 5-fluorouracil, 5-fluorouridine (5FUR), with the final purpose of co-encapsulation with doxorubicin (DOX) in liposomes. To improve the loading of 5FUR, we developed two 5FUR prodrugs that involved the conjugation of either one or three moieties of tryptophan (W) known respectively as, 5FUR−W and 5FUR−W3. 5FUR−W demonstrated greater chemical stability than 5FUR−W3 and allowed for improved loading with fewer possible byproducts from tryptophan hydrolysis. Varied drug ratios of 5FUR−W: DOX were encapsulated for in vivo testing in the highly aggressive 4T1 murine breast cancer model. A liposomal molar ratio of 2.5 5FUR−W: DOX achieved a 62.6% reduction in tumor size compared to the untreated control group and a 33% reduction compared to clinical doxorubicin liposomes in a proof-of-concept study to demonstrate the viability of the co-encapsulated liposomes. We believe that the new prodrug 5FUR−W demonstrates a prodrug design with clinical translatability by reducing the number of byproducts produced by the hydrolysis of tryptophan, while also allowing for loading flexibility.